ANALISIS DPK, CAR, ROA DAN NPF TERHADAP PEMBIAYAAN PADA PERBANKAN SYARIAH - Nurimansyah Setivia Bakti (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2017)
This research attempts to analyze the factors that affect the financing of Islamic banking in Indonesia. The independent variable in this study is the Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Return on Assets (ROA), Non Performing Financing (NPF). The sample used in this study were all population numbering Islamic Banks Islamic Banks 11. The data used in this study were obtained from published financial statements by Islamic Banks with the observation period 2013 to 2016. Based on the research result that the F test is declare that all the independent variables (independent) consisting of Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Return on Assets (ROA) and Non-Performing Financing (NPF) have a significant effect on the Financing of Islamic Banks. At t test, Third Party Funds (TPF) influence and significant to financing, the Capital Adequacy Ratio (CAR) and Return on Assets (ROA) have no significant effect on financing, while NPF has negative influence and insignificant effect on financing.